INSTITUTIONAL INFRASTRUCTURE OF LAND MORTGAGE AS A COMPONENT OF MANAGEMENT DEVELOPMENT OF AGRICULTURAL LAND USE: FOREIGN EXPERIENCE - Polishchuk, V. G. (Land Management, Cadastre and Land Monitoring, 2013)
Deals with international experience of the institutional infrastructure of the land mortgage. For working model of Ukrainian land mortgage, and finding a place in her functional land bank in Ukraine proposed to launch a pilot project for land and mort‐ gage lending on the security of land and the long term lease.